Blaming the Victim: Violence against Women in Bangladesh (The Chittagong University Journal of Social Sciences, 2025)
The present study explored the current status of blaming the Bangladeshi women by understanding the blaming motives and identifying major domineers behind blaming. The study had purposively taken into consideration of two categories of crimes, including rape and sexual harassment. Primary data were collected using the case study method and eleven severe cases were selected from twenty-nine cases of Tangail district purposively. Four types of data sources were Tangail Police Station, Tangail Court Police, several NGOs (local and nationals), and local and national newspapers. The study found that gender with power and money were significant blaming motives in the context. Most of the respondents were victimized and further blamed and repeatedly victimized by their relatives rather than strangers. Moreover, patriarchy and public attitudes were prime domineers behind blaming. Consequently, the victim had to suffer and face anger, self-blame, disability, trauma, losing life, isolation, detention, defamation, threats and verbal assault, bullying or slangs, etc.
Keywords: Blaming the victim; Rape; Sexual harassment; Patriarchy; Public attitudes; Self-blame